VD_FINDINFO HC / 2010 / 186 vom 21. Januar 2010 - VD Tribunal cantonal (2010)
VOIES DE FAIT, DIFFAMATION, TORT MORAL, AVOCAT D'OFFICE | 47 CO, 49 CO, 126 CP, 173 ch. 2 CP, 173 ch. 3 CP, 411 let. b CPP, 415 CPP